Prospective clinical study of endoscopic ultrasound‐guided biliary drainage using novel balloon catheter (with video). Issue 3 (March 2017) - Amano, Mio; Ogura, Takeshi; Onda, Saori; Takagi, Wataru; Sano, Tastsushi; Okuda, Astushi; Miyano, Akira; Masuda, Daisuke; Higuchi, Kazuhide
Abstract: Background and Aim: On endoscopic ultrasound (EUS)‐guided biliary drainage, fistula dilation may be accompanied by leakage of bile juice, potentially along with bacteria or air, so this procedure should be kept as simple and short as possible. To date, various techniques to dilate the fistula have been reported. This prospective, single‐center, single‐arm study evaluated the technical feasibility and safety of EUS‐guided biliary drainage using novel balloon catheters. Methods: Tip of novel balloon catheters is only 3 Fr and tapered, and the catheters also show favorable push ability. First, biliary tract was punctured using 19‐G fine needle aspiration needle. Next, we immediately inserted the novel balloon catheter, and the biliary tract and intestinal wall were dilated. Then, we performed metallic stent placement without any dilation fistula. Results: A total of 20 patients were prospectively enrolled in this study. Technical success rate was 100%. Eleven patients underwent EUS‐guided choledochoduodenostomy, and nine patients underwent EUS‐guided hepaticogastrostomy. Median procedure time was only 11 min (range, 8–16 min) for EUS‐guided choledochoduodenostomy and 14 min (range, 11–18 min) for EUS‐guided hepaticogastrostomy. Adverse events were seen in 15% (3/20; self‐limited abdominal pain n = 2, peritonitis n = 1). Conclusions: Although additional cases and a randomized controlled comparison with another dilation technique such as the graded dilation or cystotome dilation technique are needed, our technique may be helpful for EUS‐guided biliary drainage.